Power Flow and Short Circuit Analysis of Distribution System with 300 kW Distributed Generation Connected - Muhardika, Muhardika; Syahroni, Syahroni (Andalasian International Journal of Applied Science, Engineering and Technology, 2021)
Power flow analysis aims to determine the capacity of a generator to serve loads, to know the value of power losses in the electrical system, and to carry out a planning and development of the electric power system. Power flow analysis is carried out in order to find out the characteristics of the electric power system to be built or to be developed as desired. In this study, power flow analysis and short circuit analysis were carried out in the electrical system of Andalas University with 2 conditions, namely, when the conditions were normal or when the Distributed Generation was not added and when the conditions were added, the Distributed Generation (DG) Photovoltaic 300 kW. The results of this study indicate the largest system losses when normal conditions are on bus 1 to bus 2 amounting to 20.21 kW and 6.13 kVar, and when conditions add DG on bus 17 to bus 18 are 230.8 kW and 142.7 kVar. The results of the short circuit analysis of the two conditions are on bus 1 when the condition is experiencing the addition of DG with an increase in average current, namely 1 soil phase of 0.86 kA, 2 phases of 0.175 kA, 2 soil phases of 0.09609 kA, and 3 phases of 0.085273 kA from when the conditions were normal. Keywords : Power Flow Analysis, Short Circuit Analysis, Photovoltaic, Wind Turbine